Effect of a diffuser on performance enhancement of a cylindrical methanol steam reformer by computational fluid dynamic analysis. (15th November 2017) - Perng, Shiang-Wuu; Horng, Rong-Fang; Wu, Horng-Wen
Highlights: We enhance performance of a cylindrical MSR to get higher net power of fuel cell. We study diffuser angle and length and wall temperature on net power of fuel cell. We study methanol conversion, hydrogen production, CO of a novel reformer. Diffuser in catalyst bed upstream raises methanol conversion, hydrogen production. The MSR raises hydrogen production up to 44.6% and net fuel cell power up to 24.6%. Abstract: Proton exchange membrane fuel cells (PEMFC) connected with a methanol steam reformer designed to enhance its performance is considered as a promising future power source. Enhancing the performance of a cylindrical methanol steam reformer due to diffuser effects was then investigated applying three-dimensional computational fluid dynamics by the SIMPLE-C algorithm and an Arrhenius form of reaction model. The effect of the angle and length of the diffuser, and wall temperature have been explored on heat and fluid flow, methanol conversion, hydrogen production, carbon monoxide reduction, as well as estimated net power of fuel cell with the same catalyst volume and entrance condition in a cylindrical methanol steam reformer. The results indicate that the diffuser obviously enhances methanol conversion and hydrogen production of a cylindrical methanol steam reformer. In comparison with a traditional reformer, the reformer with a diffuser of θd  = 6° and Ld  = 75 mm obtains the maximum enhancement of 22.96% in methanol conversion, 44.62% in hydrogen production, and 24.59% in estimated net power of fuel cell at wall temperature of 250 °C. In addition, the novel reformer with a diffuser of θd  = 9° and Ld  = 100 mm generates the maximum reduction of 44.17% in CO production at TW  = 250 °C.